Automated Ocular Surface Image Analysis and Health-Related Quality of Life Utility Tool to Measure Blepharokeratoconjunctivitis Activity in Children. Issue 11 (November 2019) - Al-Hayouti, Huda; Daniel, Moritz; Hingorani, Melanie; Calder, Virginia; Dahlmann-Noor, Annegret
Abstract : Purpose: To explore the tolerability of automated conjunctival hyperemia quantification in children with blepharokeratoconjunctivitis (BKC) and its agreement with clinical activity grading and to explore the Children's Health Utility 9D (CHU9D) as a measure of health-related quality of life in children with BKC. Methods: We enrolled 63 children, 31 with BKC and 32 without ocular surface inflammation, with a median [interquartile range (IQR)] age of 10.6 (7.2–13.9) years for BKC and 11.4 (9.5–13.8) years for healthy volunteers. Two masked observers graded the ocular surface images. The children indicated discomfort during imaging on a 5-point Likert scale. Using nonparametric tests, we explored the interobserver agreement and the agreement of automated redness index (RI) measurements of limbal and bulbar conjunctival hyperemia with clinician assessment. The children also completed the 9-item CHU9D. Results: The children tolerated imaging well: median (IQR) Likert value of 0 ("comfortable") (0–0) in healthy volunteers and 1 ("a little bit uncomfortable") (0–2) in mild/moderate BKC. In children with BKC, the median (IQR) bulbar RI was 1.3 (0.8–1.6) and the median limbal RI was 0.7 (0.3–1.1). In healthy volunteers, the median bulbar RI was 0.8 (0.55–1.1; P = 0.162) and the median limbal RI was 0.3 (0.2–0.4; P = 0.02). The agreement between RI and clinical grading was high. There was no significant difference between the mean CHU9D utility score between the 2 groups [0.89 (SD 0.08) vs. 0.92 (SD 0.07); P = 0.15]. Conclusions: Automated conjunctival hyperemia quantification is feasible in children with ocular surface inflammation and may prove useful for long-term monitoring and as an objective outcome measure in clinical trials. Abstract : Supplemental Digital Content is Available in the Text.